Mechanisms and Mitigation Strategies of Gas Generation in Sodium-Ion Batteries - Li, Xingyan; Chen, Xi; Li, Meng; Wei, Haoran; Yang, Xuming; Ye, Shenghua; Li, Liewu; Chen, Jing; Ren, Xiangzhong; Ouyang, Xiaoping; Liu, Jianhong; Meng, Xiangtong; et al. (Nano-Micro Letters, 2025)
The transition to renewable energy sources has elevated the importance of SIBs (SIBs) as cost-effective alternatives to lithium-ion batteries (LIBs) for large-scale energy storage. This review examines the mechanisms of gas generation in SIBs, identifying sources from cathode materials, anode materials, and electrolytes, which pose safety risks like swelling, leakage, and explosions. Gases such as CO2, H2, and O2 primarily arise from the instability of cathode materials, side reactions between electrode and electrolyte, and electrolyte decomposition under high temperatures or voltages. Enhanced mitigation strategies, encompassing electrolyte design, buffer layer construction, and electrode material optimization, are deliberated upon. Accordingly, subsequent research endeavors should prioritize long-term high-precision gas detection to bolster the safety and performance of SIBs, thereby fortifying their commercial viability and furnishing dependable solutions for large-scale energy storage and electric vehicles. Highlights: 1 The mechanisms and main sources of gas generation in sodium-ion batteries (SIBs) are discussed. 2 In order to effectively improve the safety of SIBs, various strategies to inhibit gas generation are proposed. 3 The future development direction to enhance the safety and performance of SIBs is emphasized.